Encouraging Student’s Pro-environmental Behavior in East Beji, Depok - Kartika Nuringsih; Heni Mularsih; Edalmen Edalmen (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
The commitment to green behavior can be implemented through some activities in Raudhatul Athfal Toufiqurrahman. However, the implementation of such commitment faces two problems, namely social cultural aspects and the lifestyles of society. Differences in knowledge, educational background, and experience or lifestyle may hinder parents and teachers from being able to give proper guidance to their children and students about environment-friendly activities. Schools have limitation in organizing these activities and therefore they need to be helped. The goal of the community service program reported in this paper was to supervise teachers when introducing and evaluating environment-friendly activities. Teachers were chosen to be involved in this program so that they would be able to improve parents’ and students’ awareness about environment-friendly activities. The results showed that there was a change in students’ behavior, for example in using different types of garbage bin, in maintaining the cleanliness of the river, and in recycling unused materials for students’ crafts. However, other types of behavior such as energy-saving behavior and parents’ supervision tended to be getting lower and some were similar to those others observed before. We found that parents and students would support the green behavior movement and encourage pro-environmental behavior among kindergarten students.